PENGARUH EDUKASI PEMBERIAN KOMPRES LIDAH BUAYA TERHADAP PENGETAHUAN IBU NIFAS TENTANG BENDUNGAN ASI DI TG BALAI KARIMUN - Togatorop, Monalisa; Dwi Anjani, Arum; Fahnawal, T. Marzila (Universitas Batam, 2025)
Problems such as not producing breast milk smoothly, especially for mothers who have given birth for the first time, are very normal, and often they do not carry out IMD (Early Initiation of Breastfeeding) shortly after birth because awareness has not yet recovered, so it can be a factor in hampering the release of breast milk. To overcome this problem, you can consume papaya leaves which contain the enzymes papain and potassium, which are useful for breaking down the protein you eat, while potassium is useful for meeting potassium needs during breastfeeding. The aim is to determine the educational effect of giving stir-fried papaya leaves on postpartum mothers' knowledge about smooth breast milk production. Quantitative research method, posttest only control group design approach, January-August 2024. Place in Tanjung Balai Karimun. The study population was all postpartum mothers who were breastfeeding. The sampling technique in this research was Accidental Sampling with a total of 34 respondents. Analysis used the T Test. The average knowledge of post-partum mothers about giving stir-fried papaya leaves to facilitate breast milk production in the pretest was 14.26, posttest was 17.50, the statistical test obtained a p value = 0.001 (α < 0.05). Conclusion: There is an educational effect of giving stir-fried papaya leaves on the knowledge of postpartum mothers regarding the smooth production of breast milk Keywords : Education, Aloe Vera Compress, Postpartum, Breast Milk Dam